2014
DOI: 10.1186/1742-4682-11-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Seeking genetic signature of radiosensitivity - a novel method for data analysis in case of small sample sizes

Abstract: BackgroundThe identification of polymorphisms and/or genes responsible for an organism's radiosensitivity increases the knowledge about the cell cycle and the mechanism of the phenomena themselves, possibly providing the researchers with a better understanding of the process of carcinogenesis.AimThe aim of the study was to develop a data analysis strategy capable of discovering the genetic background of radiosensitivity in the case of small sample size studies.ResultsAmong many indirect measures of radiosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition, phosphorylation of MSH3 rs 48840878 was predicted to affect 14 different protein kinases, potentially altering the regulation of various downstream activities associated with radiotoxicity. 45 Mangoni et al, 44 also found an association between SNP rs26279 (G > A) and the development of acute skin reactions in breast cancer patients.…”
Section: Tumour Suppressor Genes-radiotoxicitymentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, phosphorylation of MSH3 rs 48840878 was predicted to affect 14 different protein kinases, potentially altering the regulation of various downstream activities associated with radiotoxicity. 45 Mangoni et al, 44 also found an association between SNP rs26279 (G > A) and the development of acute skin reactions in breast cancer patients.…”
Section: Tumour Suppressor Genes-radiotoxicitymentioning
confidence: 95%
“…Using a G2 chromosomal radiosensitivity assay, mice inbred with SNP rs 48840878 (G>A) was predicted to have an increased probability of deleterious radiosensitivity effects, although no specific endpoint was determined. In addition, phosphorylation of MSH3 rs 48840878 was predicted to affect 14 different protein kinases, potentially altering the regulation of various downstream activities associated with radiotoxicity 45 . Mangoni et al, 44 also found an association between SNP rs26279 (G>A) and the development of acute skin reactions in breast cancer patients.…”
Section: Biomarkers For Characterisation Of Patient’s Radiosensitivitmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by J. Zyla et al [ 2 ] has as the main goal the development of a data analysis strategy capable of detecting the genetic background of radiosensitivity in case of studies in which the number of samples is small. In particular, the authors used a sample of 14 inbred mouse strains, being the number of biological replicates between 1 to 3.…”
mentioning
confidence: 99%